2012
DOI: 10.1111/j.1365-2494.2012.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde content as a potential biochemical indicator of tolerant Cenchrus ciliaris L. genotypes under heat stress treatment

Abstract: Buffel grass (Cenchrus ciliaris L.) is an important forage grass in arid and semiarid regions. As part of a genetic improvement programme, four genotypes [Biloela (Bl), Americana (Am), Texas (Tx) and Sexual (Sx)] were categorized by tolerance to heat stress in a greenhouse experiment. At 30 d after sowing, half of the plants (control plants) were transferred to growth chambers (28°C day per night), and the other half (pre-treated plants, Prt) were exposed to heat stress treatment (0, 24, 48 and 72 h; 45°C day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…Methane dicarboxylic aldehyde (MDA) is a decomposition product of the polyunsaturated fatty acid hydroperoxides that are generated from reactions with ROS [ 13 ]. Hence, the MDA level is considered an indirect index of the extent of lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Methane dicarboxylic aldehyde (MDA) is a decomposition product of the polyunsaturated fatty acid hydroperoxides that are generated from reactions with ROS [ 13 ]. Hence, the MDA level is considered an indirect index of the extent of lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The content and composition of chlorophyll determines plants' absorption and utilization efficiency of different light; therefore, it is often considered an important indicator of photosynthetic physiology [25]. Many studies have indicated that allelochemicals can affect every aspect of plant growth and plants' physiological and biochemical processes [43][44][45][46][47]. An increase in inhibitory allelochemicals such as terpenes, furanones, phenol abscisic acid, coumarin, and so on, can hinder seed germination and seedling growth through physiological and biochemical processes [48].…”
Section: Discussionmentioning
confidence: 99%
“…The drastic increase in lipid peroxidation due to HT stress was reported by many researchers [162,177]. Several lines of study indicated that under heat-stress conditions, malondialdehyde (MDA), a product of peroxidation of unsaturated fatty acids, has been used as a good indicator of free radical damage to cell membranes [12,178,179]. In wheat seedlings (8-d old) gradual increase in the accumulation of H 2 O 2 was observed (0.5, 0.58, 0.78 and 1.1 μmol g -1 FW) in response to differential heat shock treatment of 22, 30, 35 and 40°C for 2 h [180].…”
Section: Oxidative Stress Under Extreme Temperaturementioning
confidence: 95%